In vitro neoformation of organs in Bixa orellana L.: morphoanatomy, cloning and characterization of pluripotency-associated putative transcription factors - Correia, Ludmila Nayara de Freitas (2016)
Pluripotency is the characteristic of plant cells that allows a single cell to originate the tissues that will compose the plant body. Organogenesis is a regeneration pathway with basis of these principles to induce organ neoformation. The plant growth hormones associated with molecular events are essential to the success of these morphogenic pathways. Thus, the objectives of this study were: to evaluate the morphogenic response in vitro from different explants of Bixa orellana submitted to organogenic induction; to characterize the cytological changes that occur during shoot and root formation, as well as to follow the mobilization of reserves, and to isolate and characterize genes expressed during the organogenic events. To assess the shoot formation, hypocotyls, injured hypocotyls, rooted hypocotyls with reversed polarity, and petiolate leaves were inoculated in JADS medium, supplemented with B5 vitamins, sucrose (3% w/v), myo- inositol (0.01% w/v), agar (0.6% w/v) and 4.56 μM zeatin, or 2.07 μM meta-topolin, or 4.14 μM meta-topolin. Samples with 0, 3, 6, 9, 18, 21, 24 and 30 days were collected for light microscopy, scanning electron microscopy, and histochemical tests following specific protocols. In order to assess the root formation, plantlets were inoculated in JADS medium in similar conditions as cited above, but with 0 or 2.46 μM indolilbutyric acid (IBA). After 0, 2, 4, 6, 8, 10, 18 and 20 days, samples were collected to perform the same analyses mentioned before. Total RNA was extracted from the organogenic material, from which the cDNA was obtained and used as a template for the amplification of coding sequences using degenerate primers for BABY BOOM (BBM) and SHOOT MERISTEMLESS (STM). It was observed that in Bixa orellana zeatin and meta-topolin induced shoot formation, but the injured hypocotyls as well as rooted hypocotyls with reversed polarity optimized the process when compared with hypocotyl and petiolate leaves. The first cell divisions were observed in the first weeks of culture in induction medium, especially in explants cultured in medium supplemented with zeatin. After 30 days of cultivation, zeatin and meta-topolin induced the formation of leaf primordia in the evaluated explants. Proteins were evidenced mainly in rooted hypocotyls and petiolate leaves. Starch grains were found in all types of explant evaluated, and a gradual increase in the concentration of this reserve compound was observed during the induction period. The neutral red test did not indicate the presence of lipids during the organogenic process. Plantlets inoculated in JADS with IBA have cell divisions after four days of culture, originating lateral root primordia. The maintenance in the induction medium supplemented with IBA for 20 days led to the formation of lateral roots. In the same period, lateral root primordia were observed in the control. The histochemical tests evidenced the presence of protein, which were consumed during the organogenic event, in addition to starch grains and lipids present in all evaluated days. Consensus sequence obtained from BBM and STM degenerate primers were cloned and sequenced. The consensus sequences obtained were compared to non-redundant protein databases NCBI, Phytozomee TAIR, using the BLAST algorithm. The analysis and alignment of sequences yielded three contigs similar to members of APETALA2-like family, especially BBM, WRINKLED (WRI) and AINTEGUMENTA (ANT), and three contigs with high similarity to transcription factors of Class I KNOX, especially STM. These results demonstrate the morphogenetic responses of different types of explants subjected to induction medium, and the possible members of the AP2-like and Class I KNOX families cloned from the analyzed sequences, which are associated with the acquisition of competence for in vitro organogenesis in Bixa orellana.